An empirical model for sedimentation of suspended solids under influence of magnetic field - Othman, Fadil; Sohaili, Johan; Fauzia, Zulfa; Niam, M. Faiqun (2006)
The magnetic treatment of wastewater is an alternative simple approach by which the wastewater that need to be treated flow through a magnetic field, and consequently some of its physicochemical properties such as suspended particles changes. The primary propose of wastewater treatment is to remove the suspended and soluble organic constituents measured as chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in the incoming liquid streams. The essence of flocculation process is the aggregation of suspended coagulated particles to form larger flocs amenable to separation from the suspending medium by some subsequent physical process, generally sedimentation. Using performance data from the application of magnetic field of 0.55 Tesla in circulation flowing system, empirical mathematical models were developed in this paper relating suspended solids (SS) removal efficiency to operating flow rate and retention time. The obtained experimental results showed that percent of SS removal increased with increasing magnetic exposure time at lower flow rates. The model coefficients were derived from the combined analysis of well correlated sets of data, thus giving a good indication for their possible general applicability. The analysis of experimental data also gave a relationship between SS and chemical oxygen demand (COD) removal efficiencies.